Relationship between Family Anxiety, Family Support and Quality of Life of Attention Defcit Hiperactivity Disorder (Adhd) Children - Adelse Prima Mulya; Helwiyah Ropi; Desy Indra Yani (Faculty of Nursing Universitas Padjadjaran, 2019)
Attenton Defcit Hiperactivity Disorder (ADHD) is behavioral disorder characterized attention defcit disorder,impulsive behavior, accompanied by excessive activity that is inconsistent with age in childhood, ADHD canimpact the decline in the quality of life of children, some of the factors that inﬂuence anxiety among families andfamily support. This study aimed to analyze the relationship between anxiety of family and family support forADHD children’s quality of life in Extraordinary school type C Bandung. The study design was cross-sectionalquantitative analytic. The subject of research totally 87 ADHD families with children aged 8-12 years who attendschool in 5 pieces of extraordinary school type C Bandung but there was something problem like rejection, nohave time and others therefore 63 samples were collected. Sampling using total sampling technique with 3 piecesinventory questionnaire including children’s quality of life questionnaire (PedsQL), family anxiety (STAI-S) andfamily support (CASSS). Data were analyzed using Pearson correlation coefcient. The results showed a correlationbetween anxiety and family support families with ADHD children’s quality of life as well as having a fairly strongcorrelation (r = 0.75 and r = 0.78). That is, an increase or decrease in the quality of life can be determined by changesin the anxiety of family and family support simultaneously. Increased family anxiety can reduce the quality of life ofchildren ADHD whereas the increase in family support can improve the quality of life of children ADHD. Nurses areexpected to increase school health services by involving schools, families and communities as well as the expectednursing policy makers in order to make policy on the procurement of health-based community health nursing school.